Analisis Pengaruh Persepsi Profesi Akuntan Publik, Motivasi Dan Kecerdasan Adversity Mahasiswa Universitas Islam Malang Terhadap Minat Menjadi Akuntan Publik - Mohammad Faizal Arif; Noor Shodiq Askandar; Abdul Wahid Mahsuni (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRACTThis study aims to determine the effect of Public Accountant Perception, Motivation and Adversity Intelligence of Malang Islamic University Students Against Interest in Becoming a Public Accountant.In this study, researchers used quantitative research methods by using primary data obtained from respondents' responses to questions on the questionnaire. The results of this study indicate the perception of public accountants, motivation and adversity intelligence simultaneously or simultaneously affect the interests of students becoming public accountants. Perception variable shows a positive influence with a sig value of 0.011 <0.05 meaning that the better the perception of students will increase interest in becoming a public accountant. Motivation variable shows a positive influence with a sig value of 0.009 <0.05 meaning that the higher the motivation of students the higher the interest in becoming a public accountant. Adversity intelligence variable shows a positive influence with a sig value of 0,000 <0.05 meaning that the higher the adversity intelligence of students the higher the interest in becoming a public accountant.Keywords: Perception, Motivation, Adversity Intelligence, Interest in Being a Public Accountant.